Radiofrequency induced heating around aneurysm clips using a generic birdcage head coil at 7 Tesla under consideration of the minimum distance to decouple multiple aneurysm clips - Noureddine, Yacine; Ladd, Mark E. (Magnetic resonance in medicine, 2019)
Purpose: To evaluate radiofrequency (RF) induced tissue heating around aneurysm clips during a 7T head MR examination and to determine the decoupling distance between multiple implanted clips. Methods: A total of 120 RF exposure scenarios of clinical relevance were studied using specific absorption rate and temperature simulations. Variations between scenarios included 2 clips (18.8 and 51.5 mm length), 2 MR-operating modes, 2 head models, and 3 thermoregulation models. Furthermore, a conservative approach was developed to allow for safe scans of patients with aneurysm clips even if detailed information on the implanted clip is unknown. A dedicated simulation-based approach was applied to determine the decoupling distance between multiple implanted clips. Results: For all 60 clinical scenarios with the 18.8-mm-long clip, the absolute tissue temperature remained below regulatory limits. For 15 of 60 scenarios with the 51.5-mm-long clip, limits were slightly exceeded (less than 1°C). The conservative approach led to a maximum time-averaged input power of the RF coil of 3.3W. The corresponding B1+ is 1.32 µT. A decoupling distance of 35 mm allows the aneurysm clips to be treated as uncoupled from one other. Conclusion: Safe scanning conditions with respect to RF-induced heating can be applied for single or decoupled aneurysm clips in a 7T ultra-high field MRI setting. Multiple aneurysm clips separated by less than 35 mm need further investigations.
Gesehen am 01.10.2019